Combined Effect of Latex and Crumb Rubber on Mechanical Properties of Concrete for Railway Application - Ang, E. H.; Lim, S. K.; King, Y. J.; Lim, J. H.; C. Tan, Andy C. (International Journal of Integrated Engineering, 2022)
Crumb rubber incorporation is widely deemed to deteriorate the compressive strength of concrete. One of the dominant reasons for this strength reduction is known as the inferior bonding or weak interfacial transition zones (ITZ) between the crumb rubber and hardened cement paste. While Styrene-butadiene (SBR) latex is being used as a bonding agent in concrete manufacturing, the SBR latex usage holds the potential to compensate for the strength reduction from crumb rubber incorporation. This study focuses on evaluating the sole and combined effect of crumb rubber and SBR latex on the compressive strength, one optimum combination of latex modified rubberised mix (LMCRC) that had achieved 55.5 MPa of 28 days characteristic strength was chosen to compare its impact resistance and stress-strain response to a plain concrete (PC) with similar characteristic strength. Experimental results showed both crumb rubber and SBR latex incorporation induced a compressive strength reduction in the concrete. The optimum latex modified rubberised mix with w/c of 0.32, crumb rubber replacement of 20kg/m3, and 3% latex additives had outperformed the control mix with w/c ratio of 0.38 by 66.7% and 293% in the 400mm span impact test and 200mm span impact test, respectively. Besides, the latex modified rubberised mix showed higher Poisson’s ratio, and higher compressive strain which indicates more ductile behaviour as compared to the plain concrete.